Hepatitis C virus infection: Diagnosis and treatment - Sultan, Md Tipu; Haque, Mahmudul; Dewanjee, Arup Kanti; Mazed, MA (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i1.3817 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):23-28